Developmental toxicity of Fe3O4 nanoparticles on cysts and three larval stages of Artemia salina. (November 2017) - Zhu, Song; Xue, Ming-Yang; Luo, Fei; Chen, Wei-Chao; Zhu, Bin; Wang, Gao-Xue
Abstract: Using Artemia salina cysts (capsulated and decapsulated) and larvae (instar I, II and III) as experimental models, the potential effects of Fe3 O4 nanoparticles (Fe3 O4 -NPs) on marine ecosystems were investigated. Hatchability, mortality and a number of ethological, morphological and biochemical parameters were selected as end-points to define the toxic responses. Data showed that the hatching rates of capsulated and decapsulated cysts were significantly decreased ( p  < 0.01) following exposure to 600 mg/L for 24 and 36 h. The LC50 values for instar II and III were 482 and 561 mg/L (could not be measured for instar I), and the EC50 values for swimming inhibition of instar I, II and III were 474, 365 and 421 mg/L, respectively. Effects on hatchability, mortality and swimming were accounted for Fe3 O4 -NPs rather than iron ion released from the NPs. Instar II larvae showed the greatest sensitivity to Fe3 O4 -NPs, and followed by instar III, instar I, decapsulated cysts and capsulated cysts. Body lengths of instar I, II and III larvae were decreased in dose-dependent manners. Fe3 O4 -NPs attached onto the gills and body surface, resulting in irreversible damages. Reactive oxygen species, malondialdehyde content, total antioxidant capacity and antioxidant enzymes (superoxide dismutase, catalase and glutathione peroxidase) activities were substantially increased following exposure, indicating that toxic effects were related to oxidative stress. Mitochondrial malformation, cristae rupturing and membranous structure disruption were clearly observed after Fe3 O4 -NPs exposure. Fe3 O4 -NPs were ingested and well distributed in the gut, yolk and primary body cavity. Uptake kinetics data showed that the maximum Fe3 O4 -NPs content (16.4 mg/g) was reached at 30 h. The combined results so far indicate that Fe3 O4 -NPs have the potential to affect aquatic organisms when released into the marine ecosystems. Graphical abstract: Highlights: Significant effects on A. salina cysts and larvae. The effects were accounted for Fe3 O4 -NPs and related to oxidative stress. Mitochondrial morphology was disrupted. Instar II larvae showed the greatest sensitivity to Fe3 O4 -NPs. Fe3 O4 -NPs were distributed in gut, yolk and primary body cavity, and the uptake kinetics was shown. Abstract : Effects of Fe3 O4 -NPs on A. salina cysts (capsulated and decapsulated) and larvae (instar I, II and III) were evaluated to elucidate the impacts on marine ecosystems.